THE EFFECT OF WORKING CAPITAL TURNOVER AND RECEIVABLES TURNOVER OF RETURN ON EQUITY: A CASE STUDY FORM COOPERATIVE - Yamin, Muhammad; Pratiwi, Aliah (Jurnal Inovasi Ekonomi, 2020)
The research aims to determine the influence of working capital turnover, receivables turnover on return on equity (ROE) at Koperasi Pegawai Negeri (KPN) "Kasabua Ade" Bima city, Indonesia. This type of research in the study uses quantitative research with purposive sampling with a 10-year sample collection and data analysis techniques using multiple regression analyses. The results showed that: 1) a partial working capital turnover level has no significant effect on ROE; 2) the receivables turnover has been partially significant to the ROE; 3) working capital turnover and receivables turnover have significant of the ROE.